2020
DOI: 10.1038/s41467-020-15343-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photolysis of H2S and its implications for SH radical production in the interstellar medium

Abstract: Hydrogen sulfide radicals in the ground state, SH(X), and hydrogen disulfide molecules, H2S, are both detected in the interstellar medium, but the returned SH(X)/H2S abundance ratios imply a depletion of the former relative to that predicted by current models (which assume that photon absorption by H2S at energies below the ionization limit results in H + SH photoproducts). Here we report that translational spectroscopy measurements of the H atoms and S(1D) atoms formed by photolysis of jet-cooled H2S molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 50 publications
7
65
0
Order By: Relevance
“…The energy required for complete dissociation of ground state H 2 S into an S( 1 D 2 ) atom and two H atoms is about 69935(25) cm –1 . 36 The corresponding two-photon energy at 291.5 nm would reach only to about 1300 cm –1 below the H 2 dissociation limit, insufficient to produce H 2 fragments in v = 13 and v = 14. A 2 + 1 REMPI spectrum of H 2 S shows a resonance at 281.8 nm, and when the dissociation laser wavelength was fixed to this resonance at 281.8 nm, the energetic region of 1000 cm –1 above the dissociation limit of H 2 can be probed and v = 13, 14 produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy required for complete dissociation of ground state H 2 S into an S( 1 D 2 ) atom and two H atoms is about 69935(25) cm –1 . 36 The corresponding two-photon energy at 291.5 nm would reach only to about 1300 cm –1 below the H 2 dissociation limit, insufficient to produce H 2 fragments in v = 13 and v = 14. A 2 + 1 REMPI spectrum of H 2 S shows a resonance at 281.8 nm, and when the dissociation laser wavelength was fixed to this resonance at 281.8 nm, the energetic region of 1000 cm –1 above the dissociation limit of H 2 can be probed and v = 13, 14 produced.…”
Section: Discussionmentioning
confidence: 99%
“…The two-photon UV-photolysis proceeds via the path: The wavelength of the dissociation laser is set at 281.8 nm, as opposed to 291 nm in the previous studies, since the energy required for complete dissociation of H 2 S to form an S( 1 D 2 ) atom and two H( 2 S) atoms is about 69935(25) cm –1 . 36 The two-photon energy for 281.8 nm dissociation lies about 1000 cm –1 above this limit, which is needed to produce H 2 in the highest vibrational levels close to the dissociation limit. Focused UV-pulses at energies of 4.5 mJ are used for the photolysis step.…”
Section: Methodsmentioning
confidence: 98%
“…The UV irradiation of H 2 S ice has most recently been revisited by Zhou et al (2020), who wished to address the apparent depletion of HS/H 2 S ratios observed in the interstellar medium relative to those predicted by contemporary models. Their experimental results revealed a wavelength dependence for the quantum yield of HS formation via H 2 S photodissociation.…”
Section: Laboratory Photochemistry Experimentsmentioning
confidence: 99%
“…The in situ ow-tube free-electron laser time of ight mass spectrometry (In situ FEL/TOF MS) were conduct at Dalian Coherent Light Source [31][32][33][34] to detect the intermediates and the radicals during methanol gas phase carbonylation reaction. Laser desorption ionization/time of ight mass spectrometry (LDI-TOF MS) was conducted to detect the dissociative fragment of spent Rh 1 /AC catalyst in normal and S-feed and further identify its single complex structure.…”
Section: Catalyst Characterizationmentioning
confidence: 99%